If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m in (-oo:+oo)
m-(5/2)-6 = 3*m-2 // - 3*m-2
m-(3*m)-(5/2)-6+2 = 0
m-3*m-5/2-6+2 = 0
-2*m-13/2 = 0 // + 13/2
-2*m = 13/2 // : -2
m = 13/2/(-2)
m = -13/4
m = -13/4
| 13y+10=26y | | 5x*4x=56+2x | | 13y+25=26 | | 13y+25=10 | | 5w^2+2w+1=0 | | x^2+6x-16=2x^2+7x-(x^2-9) | | 10x+5=13x | | 5y+3=17 | | 6.5x=52 | | 4(3x-2)-2(4x-5)=26 | | (2m-5)/3=(5m+4)/2 | | -6=-5(3t+4)+3(8-5t) | | 5x-2y=-16x | | 9x-3=2(4x+3)-3 | | 6(x+3)=3(4-x) | | -4x+9=51-3x | | 5y+3=10 | | n+3n+(3n*4)=48 | | cos(x)+cos(2x)+cos(3x)=0 | | 4z=96 | | 4a+a+(4a+a)=180 | | 3x^2+6x-11=0 | | (2x+9)(5x-7)=0 | | 9x^2-12x+4=63 | | (5x)/9+(7)/12=(1)/2 | | 3r+4=34 | | 3x^2+3y^2+6x-y=0 | | h=6lw+6wh+5hl | | -6z-6=12z+12 | | 4+i/4-i | | 4*x^2=11+y^2 | | (5x-9)(8x-7)=0 |